The Role of Selective Estrogen Receptor Modulators on Breast Cancer: From Tamoxifen to Raloxifene - Wen-Ling Lee; Ming-Huei Cheng; Hsiang-Tai Chao; Peng-Hui Wang (Elsevier, 2008)
Summary: The link between hormones and breast cancer growth and development has been recognized for more than a century. Estrogen stimulates the proliferation of breast epithelial cells, and both endogenous and exogenous estrogens have been implicated in the pathogenesis of breast cancer. Classically, estrogen action at target sites around the body is mediated through related but distinct estrogen receptors (ERs), designated ERα and ERβ, to alter gene expression. This accumulating understanding of the mechanism of action of estrogen led ultimately to the design of antiestrogenic agents that work by virtue of their interaction with the ER; these drugs have come to be known as selective estrogen receptor modulators (SERMs). Tamoxifen, a SERM, emerged as the first antiestrogenic agent that is clinically applicable to breast cancer. Tamoxifen became the "gold standard" and established the principles of tumor targeting and identified the appropriate treatment strategy to aid survivorship in breast cancer patients, with enhancement of disease-free survival and a 50% decrease in recurrences observed in ER-positive patients 15 years after diagnosis. However, because of the many adverse events in the use of tamoxifen, some of which have contributed to significant morbidity and mortality, drug modification which has resulted in fewer incidences of adverse events without compromising the therapeutic effect for breast cancer prevention may face an easier road to acceptance. Raloxifene may be a better alternative, since evidence from large clinical trials showed that raloxifene not only decreases the incidence of osteoporosis and related fractures, but also offers benefits for breast cancer prevention. The results from the Study of Tamoxifen and Raloxifene (STAR) trial showed the superiority of raloxifene over tamoxifen, not only for the equal efficacy in the prevention of invasive breast cancer but also for the fewer serious adverse events. Taken together, without other competition so far, raloxifene is recommended for postmenopausal women with osteoporosis who also need breast cancer prevention. Key Words: breast cancer, estrogen, estrogen receptor, raloxifene, selective estrogen receptor modulator, tamoxifen